2011
DOI: 10.1007/s12272-011-1121-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: SHINBARO, a new herbal medicine with multifunctional mechanism for joint disease: First therapeutic application for the treatment of osteoarthritis

Abstract: SHINBARO is a purified extract from a mixture of 6 oriental herbs (Ledebouriellae Radix, Achyranthis Radix, Acanthopanacis Cortex, Cibotii Rhizoma, Glycine Semen, and Eucommiae Cortex) that have been used as a traditional medicine for treatment of several inflammatory diseases and bone disorders. We determined antiinflammatory and antinociceptive activities of SHINBARO in adjuvant-induced (osteo)arthritis in rats. This potential anti-(osteo)arthritic property of SHINBARO can be due to the downregulation of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…A previous animal experimental study suggested that acupuncture at the lumbar region may enhance sciatic nerve blood flow as well as the peripheral vasa nervorum through regulation of blood pressure and vasodilator nerve activity, which comprises a possible mechanism for the improvement of claudication [ 14 ]. The herbs used in this study might regulate inflammatory mediators and affect the chronic inflammatory conditions of the spinal lesion [ 15 17 ]. Although Chuna manual therapy has not been shown to be as effective on LSS as chiropractic or other types of manipulation techniques [ 18 ], it might relax the shortened muscles and correct the deformity related to long-term changes in the spinal bony structures and their arrangement, contributing to the functional improvement of LSS.…”
Section: Discussionmentioning
confidence: 99%
“…A previous animal experimental study suggested that acupuncture at the lumbar region may enhance sciatic nerve blood flow as well as the peripheral vasa nervorum through regulation of blood pressure and vasodilator nerve activity, which comprises a possible mechanism for the improvement of claudication [ 14 ]. The herbs used in this study might regulate inflammatory mediators and affect the chronic inflammatory conditions of the spinal lesion [ 15 17 ]. Although Chuna manual therapy has not been shown to be as effective on LSS as chiropractic or other types of manipulation techniques [ 18 ], it might relax the shortened muscles and correct the deformity related to long-term changes in the spinal bony structures and their arrangement, contributing to the functional improvement of LSS.…”
Section: Discussionmentioning
confidence: 99%
“…The same volume of saline was used as a vehicle in control rats. The validation of SHINBARO was performed by high-performance liquid chromatography (Waters™ 600 s controller, 626 pump, temperature control module, in-line degasser, 717 plus autosampler, and 996 photodiode array detector; Waters, Bedford, MA, USA) analysis of each ingredient extract using the following six indicator biological components [ 18 ]: cimifugin for Ledebouriellae Radix; 20-hydroxyecdysone (0.311–0.312 mg/g) for Achyranthis Radix; acanthoside D (0.577–0.578 mg/g) for Acanthopanacis Cortex; onitin-4-O-β-D-glucopyranoside for Cibotii Rhizoma; genistin (0.0426–0.0427 mg/g) for Glycine Semen; and geniposide (0.431–0.432 mg/g) for Eucommiae Cortex. SHINBARO was further standardized for quality control according to the regulations imposed by the Korea Food and Drug Administration.…”
Section: Methodsmentioning
confidence: 99%
“…SHINBARO is a purified herbal formulation containing six traditional medicines, Ledebouriellae Radix ( Fang Feng ), Achyranthis Radix ( Huai Niu Xi ), Acanthopanacis Cortex ( Wu Jia Pi ), Cibotii Rhizoma ( Gou Ji ), Glycine Semen ( Hei Dou ), and Eucommiae Cortex ( Du Zhong ), that has been used to treat inflamed lesions and bone diseases [ 18 ]. Pharmacopuncture is a new form of therapy that involves both herbal medicine administration and acupuncture to manage blood extravasation and improve blood flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, EC protects cartilage by improving its metabolism, and inhibiting degradation of the ECM [35]. EC has been used as an anti-arthritic component in herbal formulations [36,37]. Achyranthes japonica Nakai (AR) has been commonly used to treat osteodynia of the knee and lumbar region, as well as spasm and flaccidity of the limbs, in traditional Korean medicine [38].…”
Section: Introductionmentioning
confidence: 99%